Case Report of an open Neck Procedure Complication Associated with Laryngeal Mask Airway Use - Thavakumar Subramaniam; Paula Casserly (Iranian Journal of Otorhinolaryngology, 2018)
Introduction: The laryngeal mask airway (LMA) is a safe method to establish airway control during general anaesthesia. In otolaryngology surgery, the use of a LMA is well established in ear surgery; however, the use of a LMA during open neck procedures remains controversial. We report a case in which the pharyngeal distortion by the LMA cuff resulted in an iatrogenic complication.   Case Report: A 38-year-old female with a background of multiple myeloma was referred to the otolaryngology team for an open cervical lymph node biopsy. The patient was in remission after a 2 year post chemotherapy treatment, but now presented with a 4-week history of persistent nodal enlargement. During the elective procedure, pharyngeal distortion from the laryngeal airway mask used for airway management resulted in an iatrogenic pharyngeal injury. This case is reported to highlight the importance of communication between the surgeon and anesthetist about the mode of airway management in open neck surgery.   Conclusion: Communication between the otolaryngologist and anesthetist is pertinent when selecting the method of airway management in open neck procedures. A LMA should be used with caution during open neck procedures, with the surgeon recognizing the potential for pharyngeal distortion.